2010
DOI: 10.1093/neuonc/nop031
|View full text |Cite
|
Sign up to set email alerts
|

High-dose carboplatin, thiotepa, and etoposide with autologous stem cell rescue for patients with previously irradiated recurrent medulloblastoma

Abstract: Recurrent medulloblastoma is highly lethal in previously irradiated patients. Previously irradiated patients with M-0-M-3 recurrences who achieved a minimal disease state prior to protocol enrollment received carboplatin (Calvert formula with area under the curve = 7 mg/mL min, maximum 500 mg/m(2)/day) on days -8 to -6, and thiotepa (300 mg/m(2)/day) and etoposide (250 mg/m(2)/day) on days -5 to -3, followed by autologous stem cell rescue (ASCR) on day 0. Twenty-five patients, aged 7.6-44.7 years (median 13.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 16 publications
6
99
0
3
Order By: Relevance
“…Recurrent medulloblastoma has a dismal prognosis (18)(19)(20)(21)(22)(23)(24). Therefore, the distinction between radiographic changes related to normal tissue damage by chemoradiotherapy and true disease progression affects the patient's subsequent treatment and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrent medulloblastoma has a dismal prognosis (18)(19)(20)(21)(22)(23)(24). Therefore, the distinction between radiographic changes related to normal tissue damage by chemoradiotherapy and true disease progression affects the patient's subsequent treatment and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Contemporaneously as well as subsequently, children with recurrent medulloblastoma, supratentorial primitive neuro-ectodermal tumor and high-grade gliomas were being treated with intensified chemotherapy including marrow-ablative chemotherapy and autologous hematopoietic cell rescue (AuHCR). [6][7][8][9][10] Furthermore, in young children relapsing after standard-dose chemotherapy regimens without irradiation, the French Society of Pediatric Oncology reported 50% EFS at a median of 31 months (n = 20) and with treatment-related mortality (TRM) at 5%. 11 Subsequently, with longer follow-up, the Memorial Sloan Kettering Cancer Center and the Children's Cancer Group (MSKCC/CCG-9883) reported in a similar cohort of young children 50% EFS at a median of 5 years and TRM at 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The use of high-dose chemotherapy with AHCR in the treatment of recurrent malignant brain tumors has been investigated with promising responses observed in patients with recurrent medulloblastoma, PNET, highgrade glioma and primary CNS germ cell tumors. 4,5,18 It has also been employed in very young children 19,20,22,23 in an attempt to avoid the deleterious long-term consequences of radiotherapy. 24 Previously successful myeloablative regimes often involved combinations of thiotepa, etoposide, carboplatin, carmustine and topotecan.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 High-dose, myeloablative chemotherapy with AHCR is frequently adopted in an attempt to improve the dismal survival rates in these patients and has shown improved outcomes when compared with standard chemotherapy treatment. 4,5 Dunkel et al 4 evaluated the use of high-dose carboplatin, thiotepa and etoposide with AHCR in adults and children with recurrent medulloblastoma, reporting event-free survivals of 34% at 3 years. Finlay et al 5 demonstrated that pediatric patients with recurrent malignant astrocytomas and minimal disease treated with thiotepa and etoposide-based chemotherapy regimens and AHCR had 4-year survival estimates of 46% compared with 0% for those treated with conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation